A remote VR operation system for a fully mechanised coal-mining face using real-time data and collaborative network technology. Issue 4 (2nd October 2018) - Xie, Jiacheng; Yang, Zhaojian; Wang, Xuewen; Wang, Yiliang
ABSTRACT: In a fully mechanised coal-mining face, the means to train machine operators are inadequate. A remote virtual reality (VR) operation system for a fully mechanised coal-mining face using real-time data and collaborative network technology is presented in this study. The overall framework and key technologies are introduced. The system comprises three mechanical components, a LAN component based on NetworkView and RPC, access to real-time data and multifunctional human–computer interaction. The proposed system solves existing operational problems, such as training on a single PC, the lack of interactive means, poor user immersion and differences between training and actual conditions. Underground operators or students can be trained using the approaches of multi-role and virtual collaboration. Finally, front- and rear-drum drivers operated the system using the centralised control centre, the shearer remote controller and the virtual panel. The proposed method can improve the actual skills of workers and effectively reduce the risk of underground mining accidents.